2020
DOI: 10.14358/pers.86.7.431
|View full text |Cite
|
Sign up to set email alerts
|

Improved Crop Classification with Rotation Knowledge using Sentinel-1 and -2 Time Series

Abstract: Leveraging the recent availability of accurate, frequent, and multimodal (radar and optical) Sentinel-1 and -2 acquisitions, this paper investigates the automation of land parcel identi- fication system (LPIS ) crop type classification. Our approach allows for the automatic integration of temporal knowledge, i.e., crop rotations using existing parcel-based land cover databases and multi-modal Sentinel-1 and -2 time series. The temporal evolution of crop types was modeled with a linear- chain condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]). Such synergistic approaches consistently showed better overall accuracies than monosensor classifications (e.g., [48,51,56,57]), particularly in the case of challenging cloud situations [49].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the potential to map crop types based on Sentinel-1 time series without additional optical data input in Europe (e.g., [30][31][32][33][34][35][36][37][38][39][40][41]) and in Germany (e.g., [42][43][44]). However, particularly promising are approaches combining optical and SAR data (e.g., for Asia [45], Africa [46,47], Europe [48][49][50][51][52][53][54][55], and Germany [56][57][58]). Such synergistic approaches consistently showed better overall accuracies than monosensor classifications (e.g., [48,51,56,57]), particularly in the case of challenging cloud situations [49].…”
Section: Introductionmentioning
confidence: 99%
“…Osman et al [31] propose to use probabilistic Markov models to predict the most probable crop type from the sequence of past cultivated crops of the previous 3 to 5 years. Giordano et al [32] and Bailly et al [33] propose to model the multi-year rotation with a second order chain-Conditional Random Field (CRF). Finally, Yaramasu et al [34] were the first to propose to analyze multi-year data with a deep convolutional-recurrent model.…”
Section: Multi-year Crop Type Classificationmentioning
confidence: 99%
“…Conditional Random Fields: M CRF . Based on the work of [32,33], we implement a simple chain-CRF probabilistic model. We use the prediction of the previous PSE+LTAE, calibrated with the method of Guo et al [40] to approximate the posterior probability p ∈ [0, 1] L of a parcel having the label k for year i:p k = P(l i = k | x i ) (see Section 3.3 for more details).…”
Section: Baseline Modelsmentioning
confidence: 99%
“…Osman et al [24] propose to use probabilistic Markov models to predict the most probable crop type from the sequence of past cultivated crops of the previous 3 to 5 years. Giordano et al [14] and Bailly et al [3] propose to model the multi-year rotation with a second order chain-Conditional Random Field (CRF). Finally, Yaramasu et al [38] were the first to propose to analyze multi-year data with a deep convolutional-recurrent model.…”
Section: 2020mentioning
confidence: 99%
“…Conditional Random Fields: M CRF . Based on the work of [3] and [14], we implement a simple chain-CRF probabilistic model. We use the prediction of the previous PSE+LTAE, calibrated with the method of Guo et al [15] to approximate the posterior probability p ∈ [0, 1] L of a parcel having the label k for year i : p k = P (l i = k | x i ) (see Section 3.4 for more details).…”
Section: Baseline Modelsmentioning
confidence: 99%